The Development of STEM-Based Teaching Materials to Improve Science Literacy for Grade III Elementary School Students - Henni Marsari; Rifma Rifma (STAI Hubbulwathan Duri, 2023)
21st-century learning requires teachers to deliver students to 4C skills in facing the Industrial Revolution 4.0. This study aims to develop valid, practical, and effective STEM teaching materials for Grade III Elementary schools. It is development research with the ADDIE model and a total of 58 third-grade elementary school students as the research subject from three elementary schools in West Pasaman Regency. The research data is from developing STEM teaching materials for grade III Elementary school. The results of the data analysis of the validation of teaching materials by experts and education practitioners obtained an average of 92.7 very valid categories. The results of the practicality test using teacher and student questionnaires obtained an average of 92.85 and 92.93 with very practical categories. The effectiveness of these teaching materials is also shown by the increase in the average scientific literacy of students after using STEM teaching materials is 87, with a very effective category. Based on the results above, it can be concluded that the STEM material for grade III elementary school is declared to be very valid, very practical, and effectively used to improve students' scientific literacy in grade III of elementary school